VIEWS ON LEARNING IN DIFFERENT CULTURES. COMPARING PATTERNS IN CHINA AND URUGUAY - Marton, Ference; Wen, Qiufang; Nagle, Alberto (Anales de Psicología / Annals of Psychology)
This paper reports findings from a comparative study of conceptions of learning amongst Chinese and Uruguayan students. The results were obtained through reanalyzing the interview data of two independent studies. This comparative re-analysis was undertaken in line with the general framework proposed by Marton, Watkins and Tang (in press) in which different conceptions of learning are structured along two dimensions, i.e. a temporal dimension (acquiring-knowing-applying) and depth of learning (surface-deep).The results showed that both Chinese and Uruguayan students emphasized the acquisition phase of learning and furthermore, they shared the view that learning was always initiated by obtained knowledge. However, almost none of the subjects explained how they went about the initial action of learning. The views expressed by the two groups appeared contradictory in many cases but turned out to be complementary once they were seen in terms of the aforesaid framework. The Chinese students tended to emphasize the on-going aspect of learning and Uruguayans the act of making the knowledge obtained permanent within themselves. The Chinese students singled out the act of committing what they have read or told to their memory as a necessary step in learning while the Uruguayan students didn‘t think such a conscious act was necessary because keeping things in the memory was regarded as a natural byproduct of learning. The Chinese students stressed outer behaviors such as repeated practice more and the Uruguayan students inner behaviors such as assimilating, incorporating and selfexperiencing. Finally, the Chinese students saw memorization as being of two kinds: mechanical and meaningful, the latter being interrelated with understanding, while the Uruguayan students simply equated memorization with rote learning and saw it as opposite to understanding.